Oral Delivery of a Synthetic Sterol Reduces Axonopathy and Inflammation in a Rodent Model of Glaucoma - Lambert, Wendi S.; Carlson, Brian J.; Formichella, Cathryn R.; Sappington, Rebecca M.; Ahlem, Clarence; Calkins, David J. (Frontiers in Neuroscience, 2017)
Glaucoma is a group of optic neuropathies associated with aging and sensitivity to intraocular pressure (IOP). The disease is the leading cause of irreversible blindness worldwide. Early progression in glaucoma involves dysfunction of retinal ganglion cell (RGC) axons, which comprise the optic nerve. Deficits in anterograde transport along RGC axons to central visual structures precede outright degeneration, and preventing these deficits is efficacious at abating subsequent progression. HE3286 is a synthetic sterol derivative that has shown therapeutic promise in models of inflammatory disease and neurodegenerative disease. We examined the efficacy of HE3286 oral delivery in preventing loss of anterograde transport in an inducible model of glaucoma (microbead occlusion). Adult rats received HE3286 (20 mg/kg or 100 mg/kg) or vehicle daily via oral gavage for four weeks. Microbead occlusion elevated IOP ~30% in all treatment groups, and elevation was not affected by HE3286 treatment. In the vehicle group, elevated IOP reduced anterograde axonal transport to the superior colliculus, the most distal site in the optic projection, by 43% (p = 0.003); HE3286 (100 mg/kg) prevented this reduction (p = 0.025). HE3286 increased brain-derived neurotrophic factor (BDNF) in the optic nerve head and retina, while decreasing inflammatory and pathogenic proteins associated with elevated IOP compared to vehicle treatment. Treatment with HE3286 also increased nuclear localization of the transcription factor NF-kappa B in collicular and retinal neurons, but decreased NF-kappa B in glial nuclei in the optic nerve head. Thus, HE3286 may have a neuroprotective influence in glaucoma, as well as other chronic neurodegenerations.